The implementation of the promotion mix on cash waqf collection / Alvien Nur Amalia - Alvien, Nur Amalia (UiTM Cawangan Johor, 2019)
The cash waqf collection requires a strategic step in its improvement. One of the strategies is the promotion mix. Promotion mix is not only for profit-oriented organizations but also for non-profits. One of the waqf institutions that managed to raise waqf funds and have productive waqf programs is the Al AzharWaqf Institution. They fund their productive waqf programs used cash waqf. Therefore, the process of collecting cash waqf is important. The purpose of this study was to analyze the implementation of the promotion mix for collecting cash waqf at the Al AzharWaqf Institution. The interview technique is used to obtain primary data, then analyzed through a qualitative methodology approach. The results of the study indicate that the Al AzharWaqf Institution used a promotional mix in collecting cash waqf. The promotion mix includes both direct and indirect promotions that are used to inform productive waqf programs to the waqf.